Crosslinked polyolefin rubber material for high-voltage energy supply system and cable preparation method
By designing a crosslinked polyolefin material for high-voltage energy supply system, combined with reasonable raw material ratio and processing technology, the problem that existing wires are difficult to meet multiple performance requirements at the same time is solved, and the high-voltage power cable is realized Multiple performance improvements are suitable for high-voltage energy supply systems for new energy vehicles.
Patent Information
- Application Number
- CN202411459138.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-21
AI Technical Summary
Existing high-voltage power cords are difficult to meet the temperature resistance grade, insulation tensile strength, elongation and flame retardant performance requirements of German standard ISO19642 and American standard UL1581 required for new energy vehicles at the same time.
A crosslinked polyolefin material for high-pressure energy supply system was designed, including high-elastic ethylene-vinyl acetate copolymer EVA, vinyl alcohol rubber, aluminum hypophosphate, magnesium hydroxide, melamine cyanurate, coupling agent, anti- Oxygen and lubricant ensure excellent performance of the cable through reasonable raw material ratio and processing technology.
It realizes that high-voltage power cables meet the temperature resistance level of -40℃~125℃, insulation tensile strength ≥1.41kgf/mm2, elongation ≥300% and flame retardant performance of German standard ISO19642 and American standard UL1581, and meets VW- 1. It is required and does not contain halogen, and has little ecological toxicity to the environment.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cable rubber compounds, and in particular to a cross-linked polyolefin rubber compound and a cable preparation method for a high-voltage energy supply system. Background Art
[0002] With the development of new energy vehicles, the performance of halogen-free 125℃ grade XLPE rubber compounds currently used in the field of high-voltage power lines for new energy vehicles can meet the automotive line standard ISO19642, but cannot be applied to the UL standard, mainly because the performance requirements of UL125℃ aging and VW-1 are relatively high. When halogen-free rubber compounds are used to make small square wire gauges, in order to meet the flame retardant properties of VW-1, the filling amount is extremely high, resulting in the temperature resistance level being unable to reach the UL125℃ level, and the tensile strength and elongation residual rate cannot meet the standard requirements after aging. With the development of the market, more and more customers demand new energy wires that meet both automotive line standards and UL standards. For this reason, the above-mentioned high-voltage power supply cables that meet the above-mentioned requirements are designed and developed. Summary of the invention
[0003] In order to solve the above technical problems, the present application provides a cross-linked polyolefin rubber for a high-voltage energy supply system, which includes the following components, measured by mass: 20 to 80 parts of high-elastic ethylene-vinyl acetate copolymer EVA, 20 to 40 parts of ethylene-vinyl acetate rubber EVM, 5 to 10 parts of diethyl aluminum hypophosphite, 60 to 70 parts of magnesium hydroxide, 10 to 20 parts of melamine cyanurate, 4 to 8 parts of coupling agent, 4 to 8 parts of antioxidant, and 5 to 6 parts of lubricant. By designing appropriate raw material components, material ratios, and by designing processing technology and processing parameters in coordination, the cable has the best performance, so that the high-voltage power cable meets the -40℃~125℃ temperature resistance level of German standard ISO19642 and American standard UL1581 at the same time, with insulation tensile strength ≥1.41kgf / mm2, elongation ≥300%, excellent flame retardant performance, meeting VW-1 requirements and automotive line standards, and the cross-linked polyolefin rubber does not contain halogen and has low eco-toxicity to the environment, so it can be used in the high-voltage energy supply system of new energy vehicles.
[0004] Preferably, the brand of the high elastic ethylene-vinyl acetate copolymer EVA is DuPont 265, wherein the vinyl acetate content is 28.0wt%, and the melt index is 3g / 10min.
[0005] Preferably, the grade of the ethylene-vinyl acetate rubber (EVM) is EVM 500.
[0006] Preferably, the coupling agent is isopropyl alkoxypyrophosphoryloxytitanate.
[0007] Preferably, the lubricant comprises silicone powder.
[0008] Preferably, a method for preparing a cable is prepared by using the cross-linked polyolefin rubber material for the high-voltage energy supply system, comprising the following steps:
[0009] S100: weighing high elastic ethylene-vinyl acetate copolymer EVA, ethylene ethylene rubber, diethyl aluminum hypophosphite, melamine cyanurate, coupling agent and antioxidant according to component ratio, and dividing high elastic ethylene-vinyl acetate copolymer EVA, ethylene ethylene rubber, diethyl aluminum hypophosphite and melamine cyanurate into two groups for standby use;
[0010] S200: putting the first group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene butyl rubber, diethyl aluminum hypophosphite and melamine cyanurate into a vacuum kneader, kneading at a speed of 20 to 35 r / min, mixing at 130 to 140° C. for 10 to 15 minutes, and a vacuum pressure of 0.8 to 0.9 MPa;
[0011] S300: raising the temperature of the vacuum kneader to 150°C to 155°C, adding the second group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene valerium rubber, diethyl aluminum hypophosphite and melamine cyanurate, as well as all coupling agents and antioxidants into the vacuum kneader, and mixing for 15 to 20 minutes;
[0012] S400: adding magnesium hydroxide and lubricant into the vacuum kneader, mixing for 5-10 minutes, and then heating to 160° C. and mixing for 20-25 minutes to obtain a mixture;
[0013] S500: conveying the kneaded mixture to a single screw extruder at a feeding speed of 30-40 r / min, an extrusion temperature of 150-165° C., a screw speed of 70-100 r / min, and a line speed of 30-40 m / min. After extrusion, pelletizing and air cooling are performed to obtain a cross-linked polyolefin rubber compound.
[0014] S600: After drying the cross-linked polyolefin rubber, put it into the wire extruder. When the extrusion line speed is 40-60m / min, the screw speed is 250-350r / min, the temperature of the conveying, compression and metering sections is 160-175℃, the conductor preheating temperature is 90-100℃, an insulating layer is extruded around the conductor to form an insulating layer, and then it is irradiated and cross-linked with a cross-linking dose of 14M to obtain a finished cable.
[0015] Preferably, the wire diameter of the finished cable is 4.1-4.3 mm, and the insulation thickness is 0.68-0.8 mm.
[0016] Preferably, the outer diameter φ of the wire extrusion screw used in step S600 is 70 mm, the aspect ratio is 1:(24-25), and the compression ratio is 2.
[0017] From the above, it can be seen that the application provided by this application can obtain the following beneficial effects: by designing suitable raw material components, material ratios, and by designing processing technology and processing parameters in coordination, the cable has the best performance, so that the high-voltage power supply cable meets the -40°C to 125°C temperature resistance level of the German standard ISO19642 and the American standard UL1581 at the same time, the insulation tensile strength is ≥1.41kgf / mm2, the elongation is ≥300%, the flame retardant performance is excellent, and the VW-1 requirements and automotive line standards are met. The cross-linked polyolefin rubber does not contain halogen and has low eco-toxicity to the environment, and can be used in the high-voltage energy supply system of new energy vehicles. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0019] Example 1
[0020] In order to solve the above technical problems, the present embodiment provides a cross-linked polyolefin rubber for a high-voltage energy supply system, which includes the following components, by mass: 20 to 80 parts of high-elastic ethylene-vinyl acetate copolymer EVA, 20 to 40 parts of ethylene-vinyl acetate rubber EVM, 5 to 10 parts of diethyl aluminum hypophosphite, 60 to 70 parts of magnesium hydroxide, 10 to 20 parts of melamine cyanurate, 4 to 8 parts of coupling agent, 4 to 8 parts of antioxidant, and 3 to 6 parts of lubricant.
[0021] Specifically, the brand of the high elastic ethylene-vinyl acetate copolymer EVA is DuPont 265, wherein the vinyl acetate content is 28.0wt%, and the melt index is 3g / 10min.
[0022] Furthermore, the grade of EVM is EVM 500. The coupling agent is alkoxy pyrophosphoryloxy titanate isopropyl. The lubricant includes silicone powder.
[0023] Specifically, the specific components of the raw materials in this embodiment are: 80 parts of high-elastic ethylene-vinyl acetate copolymer EVA, 20 parts of ethylenediamine rubber EVM, 10 parts of diethyl aluminum hypophosphite, 60 parts of magnesium hydroxide, 20 parts of melamine cyanurate, 8 parts of coupling agent, 8 parts of antioxidant, and 3 parts of lubricant.
[0024] This embodiment provides a method for preparing a cable, which is prepared by using the cross-linked polyolefin rubber material for the high-voltage energy supply system, and includes the following steps:
[0025] S100: weighing high elastic ethylene-vinyl acetate copolymer EVA, ethylene ethylene rubber, diethyl aluminum hypophosphite, magnesium hydroxide, melamine cyanurate, coupling agent and antioxidant according to component ratio, and dividing high elastic ethylene-vinyl acetate copolymer EVA, ethylene ethylene rubber, diethyl aluminum hypophosphite and melamine cyanurate into two groups for standby use;
[0026] S200: putting the first group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene butyl rubber, diethyl aluminum hypophosphite and melamine cyanurate into a vacuum kneader, kneading at a speed of 20 to 35 r / min, mixing at 130 to 140° C. for 10 to 15 minutes, and a vacuum pressure of 0.8 to 0.9 MPa;
[0027] In this step, the first group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene terephthalate rubber, diethyl aluminum hypophosphite and melamine cyanurate are put into a vacuum kneader at a kneading speed of 35 r / min, mixing at 130° C. for 10 min and a vacuum pressure of 0.8 MPa.
[0028] S300: raising the temperature of the vacuum kneader to 150°C to 155°C, adding the second group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene valerium rubber, diethyl aluminum hypophosphite and melamine cyanurate, as well as all coupling agents and antioxidants into the vacuum kneader, and mixing for 15 to 20 minutes;
[0029] The temperature of the vacuum kneader in this step is raised to 150° C., the mixing time is 15 min, and the kneading speed and vacuum pressure are the same as those in step S200. In steps S200-S300, high elastic ethylene-vinyl acetate copolymer EVA, ethylene valerian rubber, diethyl aluminum hypophosphite and melamine cyanurate are mixed in batches to achieve uniform dispersion and mixing of the raw materials, so that the raw materials are fully mixed, thereby improving the performance of the rubber compound under the synergistic effect of various components.
[0030] S400: adding magnesium hydroxide and lubricant into the vacuum kneader, mixing for 5-10 minutes, and then heating to 160° C. and mixing for 20-25 minutes to obtain a mixture;
[0031] Finally, in step S400, magnesium hydroxide and lubricant are added, mixed for 10 minutes, and then the temperature is raised to 160°C and mixed for 20 minutes to finally obtain a mixture.
[0032] S500: conveying the kneaded mixture to a single screw extruder with a feeding speed of 30-40 r / min, an extrusion temperature of 150-165°C, a screw speed of 70-100 r / min, and a line speed of 30-40 m / min. After extrusion, pelletizing and air cooling are performed to obtain a cross-linked polyolefin rubber compound; wherein, the feeding speed is 40 r / min, the extrusion temperature is 165°C, the screw speed is 100 r / min, and the line speed is 40 m / min.
[0033] S600: After drying the cross-linked polyolefin rubber, put it into the wire extruder, with the extrusion line speed of 40-60m / min, the screw speed of 250-350r / min, the temperature of the conveying, compression and metering section of 160-175℃, the conductor preheating temperature of 90-100℃, and extrude the insulation layer on the outer periphery of the conductor, and then cross-link it with radiation, and the cross-linking dosage is 14M to obtain the finished cable. Among them, the extrusion line speed is 40m / min, the screw speed is 250r / min,
[0034] The wire diameter of the finished cable is 4.1-4.3 mm, and the insulation thickness is 0.68-0.8 mm. The outer diameter φ of the wire extrusion screw used in step S600 is 70 mm, the aspect ratio is 1:(24-25), preferably 1:25, and the compression ratio is 2.
[0035] Example 2
[0036] The raw material components of this embodiment 2 are: 80 parts of high elastic ethylene-vinyl acetate copolymer EVA, 20 parts of ethylene valerium rubber EVM, 10 parts of diethyl aluminum hypophosphite, 60 parts of magnesium hydroxide, 20 parts of melamine cyanurate, 8 parts of coupling agent, 8 parts of antioxidant, and 3 parts of lubricant. Different from embodiment 1, the brand of ethylene-vinyl acetate copolymer EVA used in this embodiment 2 is conventional Formosa Plastics 7370K, in which the vinyl acetate content is 18.0wt%. The preparation method is the same as that of embodiment 1 to obtain a finished cable product.
[0037] Example 3
[0038] The raw material components of this embodiment 3 are: 60 parts of high elastic ethylene-vinyl acetate copolymer EVA, 40 parts of ethylene ethylene rubber EVM, 10 parts of diethyl aluminum hypophosphite, 60 parts of magnesium hydroxide, 20 parts of melamine cyanurate, 8 parts of coupling agent, 8 parts of antioxidant, and 3 parts of lubricant. Different from embodiment 1, the high elastic ethylene-vinyl acetate copolymer EVA of this embodiment 3 is adjusted to 60 parts, and the ethylene ethylene rubber EVM is adjusted to 40 parts. The preparation method is the same as that of embodiment 1 to obtain a finished cable product.
[0039] Example 4
[0040] The raw material components of this embodiment 4 are: 80 parts of high elastic ethylene-vinyl acetate copolymer EVA, 10 parts of diethyl aluminum hypophosphite, 60 parts of magnesium hydroxide, 20 parts of melamine cyanurate, 8 parts of coupling agent, 8 parts of antioxidant, and 3 parts of lubricant. Different from embodiment 1, this embodiment 4 does not add ethylene vanta rubber EVM and adjusts it to 40 parts. The preparation method is the same as that of embodiment 1 to obtain a finished cable product.
[0041] Example 5
[0042] The raw material components of this embodiment 5 are the same as those of embodiment 1. The difference from embodiment 1 is that in step S500, the kneaded mixture is conveyed to a single screw extruder with a feeding rate of 20 r / min, a screw speed of 60 r / min, and a line speed of 20 m / min. After extrusion, the mixture is pelletized and air-cooled to obtain a cross-linked polyolefin rubber compound.
[0043] Example 6
[0044] The raw material components of this embodiment 2 are the same as those of embodiment 1. The difference between this embodiment 2 and embodiment 1 is that in the preparation method of this embodiment 2, all the raw materials are put into a vacuum kneader for mixing, and the mixing temperature is directly increased to 160° C., and the mixing time is 40 minutes.
[0045]
[0046]
[0047] Table 1 Table 1 is a table of ingredients for Examples 1-6.
[0048]
[0049] Table 2 Table 2 shows the UL performance test results of the cable samples of various embodiments.
[0050]
[0051] Table 3
[0052] Table 3 shows the ISO performance test results of the cable samples of various embodiments.
[0053] From the test results in Table 2 and Table 3, it can be seen that the EVA in Example 1 uses DuPont with a vinyl acetate content of 28.0 wt%. 265, the tensile strength and elongation at break of the cable produced by it are excellent, while the tensile strength and elongation at break of the cable produced by Formosa Plastics 7370K used in Example 2 are unqualified. The tensile strength of 265 is greater than that of Formosa Plastics 7370K. After being made into composite materials, the tensile strength of the two materials loses the same value. DuPont 265 EVA can ensure that the tensile strength of the wire is still above the standard line. At the same time, by comparing Example 1 and Example 3, it can be seen that the amount of EVA in Example 3 is less than that in Example 1, while the amount of EVM is increased. At this time, although the tensile strength and elongation at break of Example 3 are qualified, they are much worse than those of Example 1. It can be seen that designing the appropriate amount of EVA plays a vital role in the tensile strength and elongation at break of the wire.
[0054] By comparing Example 1 and Example 4, it can be seen that the flame retardant of Example 4 uses Mg(OH)2 alone, lacking the synergistic effect of ADP and MCA, so that the flame retardancy of the finished cable is unqualified. At the same time, the cable's water and heat resistance, long-term aging resistance, tensile strength and elongation at break are all unqualified, proving that the appropriate proportion and dosage of Mg(OH)2, ADP and MCA can improve the performance of the wire in many aspects.
[0055] By comparing Example 1 and Example 5, it can be seen that the difference between Example 1 and Example 5 is that the process conditions for granulating the rubber material are different. From the test results, it can be seen that the lower the feeding speed and the extrusion speed, the worse the plasticizing effect, the rougher the appearance of the manufactured cable insulation, and the low-temperature winding is unqualified. Therefore, the design of the extruder process parameters has an impact on the appearance of the cable insulation.
[0056] Comparing Example 1 and Example 6, it can be seen that the difference between Example 1 and Example 6 lies in the different mixing processes of the raw materials. Example 6 does not use batch addition and mixing, resulting in insufficient dispersion of the rubber material, which leads to poor plasticization, and ultimately leads to a rough appearance of the cable and unqualified low-temperature winding. In Example 1, each raw material is added in batches and mixed evenly, so that each raw material is fully dispersed and mixed, so that the appearance of the manufactured cable sheath is more delicate. The performance of the cable in Example 1 in terms of tensile strength, elongation at break and temperature resistance is much better than that in Example 6. Therefore, the mixing process has a greater impact on the appearance and performance of the finished product.
[0057] In summary, Example 1 is the best implementation method of the present application. By designing appropriate raw material components, material ratios, and by designing processing technology and processing parameters in coordination, the cable has the best performance, so that the high-voltage power supply cable meets the -40°C to 125°C temperature resistance level of the German standard ISO19642 and the American standard UL1581 at the same time, the insulation tensile strength is ≥1.41kgf / mm2, the elongation is ≥300%, the flame retardant performance is excellent, and the VW-1 requirements are met. The cross-linked polyolefin rubber does not contain halogen and has low eco-toxicity to the environment, and can be used in the high-voltage energy supply system of new energy vehicles.
[0058] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.
Claims
1. A cross-linked polyolefin rubber material for a high-voltage energy supply system, characterized in that: The composition comprises the following components in parts by mass: 20 to 80 parts of high elastic ethylene-vinyl acetate copolymer EVA, 20 to 40 parts of ethylene-vinyl acetate rubber EVM, 5 to 10 parts of diethyl aluminum hypophosphite, 60 to 70 parts of magnesium hydroxide, 10 to 20 parts of melamine cyanurate, 4 to 8 parts of coupling agent, 4 to 8 parts of antioxidant and 3 to 6 parts of lubricant.
2. The cross-linked polyolefin rubber material for the high-voltage energy supply system according to claim 1, characterized in that: The brand of the high elastic ethylene-vinyl acetate copolymer EVA is DuPont 265, wherein the vinyl acetate content is 28.0wt%, and the melt index is 3g / 10min.
3. The cross-linked polyolefin rubber material for the high-voltage energy supply system according to claim 1, characterized in that: The grade of the EVM is EVM 500.
4. The cross-linked polyolefin rubber material for the high-voltage energy supply system according to claim 1, characterized in that: The coupling agent is isopropyl alkoxypyrophosphoryl titanate.
5. The cross-linked polyolefin rubber material for the high-voltage energy supply system according to claim 1, characterized in that: The lubricant includes silicone powder.
6. A cable preparation method, characterized in that: The method is prepared by using the cross-linked polyolefin rubber material for the high-voltage energy supply system according to any one of claims 1 to 5, comprising the following steps: S100: weighing high elastic ethylene-vinyl acetate copolymer EVA, ethylene ethylene rubber, diethyl aluminum hypophosphite, magnesium hydroxide, melamine cyanurate, coupling agent and antioxidant according to component ratio, and dividing high elastic ethylene-vinyl acetate copolymer EVA, ethylene ethylene rubber, magnesium hydroxide, diethyl aluminum hypophosphite and melamine cyanurate into two groups for standby use; S200: putting the first group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene butyl rubber, diethyl aluminum hypophosphite and melamine cyanurate into a vacuum kneader, kneading at a speed of 20 to 35 r / min, mixing at 130 to 140° C. for 10 to 15 minutes, and a vacuum pressure of 0.8 to 0.9 MPa; S300: raising the temperature of the vacuum kneader to 150°C to 155°C, adding the second group of high elastic ethylene-vinyl acetate copolymer EVA, ethylene valerium rubber, diethyl aluminum hypophosphite and melamine cyanurate, as well as all coupling agents and antioxidants into the vacuum kneader, and mixing for 15 to 20 minutes; S400: adding magnesium hydroxide and lubricant into the vacuum kneader, mixing for 5-10 minutes, and then heating to 160° C. and mixing for 20-25 minutes to obtain a mixture; S500: conveying the kneaded mixture to a single screw extruder at a feeding speed of 30-40 r / min, an extrusion temperature of 150-165° C., a screw speed of 70-100 r / min, and a line speed of 30-40 m / min. After extrusion, pelletizing and air cooling are performed to obtain a cross-linked polyolefin rubber compound. S600: After drying the cross-linked polyolefin rubber, put it into the wire extruder. When the extrusion line speed is 40-60m / min, the screw speed is 250-350r / min, the temperature of the conveying, compression and metering sections is 160-175℃, the conductor preheating temperature is 90-100℃, an insulating layer is extruded around the conductor to form an insulating layer, and then it is irradiated and cross-linked with a cross-linking dose of 14M to obtain a finished cable.
7. The cable preparation method according to claim 6, characterized in that: The wire diameter of the finished cable is 4.1-4.3 mm, and the insulation thickness is 0.68-0.8 mm.
8. The cable preparation method according to claim 6, characterized in that: The outer diameter φ of the wire extrusion screw used in step S600 is 70 mm, the aspect ratio is 1:(24-25), and the compression ratio is 2.